Pengembangan Media Video Tutorial Zero Waste Pattern Blus Banesa Melalui YouTube - Niluk Rozalia Asyari; Irma Russanti (Journal on Education, 2023)
Textile production waste is the largest waste contributor. With the innovation of the zero waste pattern, it can reduce waste from textile production. YouTube is a very interesting platform so that with an educational video tutorial on making the zero waste pattern blouse with banesa batik, it can direct YouTube users to wear clothes that have minimal waste processing. The purpose of this study was to find out 1) the validity level of the tutorial video for making zero waste pattern blouses using Unesa batik basic materials 2) to find out the response of YouTube users to the video tutorial for making zero waste pattern blouses using Unesa batik basic materials. The research method used is research and development (Research and Development) with the ADDIE development model. The data collection technique in this study used the validity test method to determine the validity level of the video tutorial on making zero waste pattern blouses using Unesa batik as the basic material. Based on data analysis techniques, the results showed that 1) the level of validity reviewed by material experts scored 76.92% and by media experts it was 85% with an average of 81% included in the "very feasible" category 2) response YouTube users get an average value of 82.5% from 50 YouTube user respondents. Thus, it can be concluded that the tutorial video for making zero waste pattern blouse patterns using Unesa batik as the basic material is "very feasible" to be used as media and gets a "very good" response from YouTube users.